Study of the Seed and Oil Yield of the Jatropha Plant Grown in Tartous (Syria) (Latakia University Journal -Biological Sciences Series, 2021)
In this research, the seed and oil production and the most important properties of the oil of the introduced plant "Jatropha" were studied at Al-Thawra agricultural site (15 m above sea level) during two fruiting years, the first one (about two years old) and the second (about three years old) for fruiting.The results showed weak seed production during the first fruiting year. The result for no pruning/ no weeding treatment and for weeding only treatment was 0.002 kg/ plant, for pruning and weeding treatment and for pruning treatment was 0.003 kg/ plant. In the second fruiting year, the result for non-pruning/ non-weeding trees was 0.008 kg/ plant, for weeding trees was 0.005 kg/ plant, for pruning/ weeding trees was 0.01 kg/ plant, and for pruning trees 0.008 kg/ plant. The oil yield of the native Jatropha trees was good (36.36 % of the seed weight) and much better than the yield of the experimental field in the same year (21.75 %), and the yield of the experimental field in its second fruiting year.The decline in fruit and oil yield was mainly because the field soil is poor in nutrients, and the absence of agricultural service operations such as fertilization and irrigation. The age increase was not reflected in an increase in the oil content of the seeds during the first two years of fruiting.Jatropha oil extracted from the experiment field is considered an inedible oil due to its high acidity, as its value was not less than 12 mg KOH / g, and an impure oil in which the peroxide level was not less than the reference 49 meq/ kg. On the other hand, the value of saponification decreased and did not exceed 40.9 mg/ g for the oil.